STUDI KRITIS ATAS PEMIKIRAN HADIS MAHMUD ABU RAYYAH: Riwayat bi al-Ma’na, Kredibiltas Abu Hurayrah Tentang Kolektor Hadis Terbanyak - Engkus Kusnandar (UIN Siber Syekh Nurjati Cirebon, 2022)
The following article examines the thought of the hadith of Mahmud Abu Rayyah. His thoughts and views on the sunnah of the Prophet SAW are listed in two of his works, Adwa ’ala al-Sunah al-Muhammadiyah, and Shaykh al-Mudhirah: Abu Hurayrah al-Dawsi. This paper examines his thoughts on hadith, as well as critiques the number of negative views of the prophet's hadith regarding the bi al-ma’na history, and the credibility of Abu Hurayrah as the largest hadith collector. This study aims to criticize the negative views of Abu Hurayrah and those who believe in it, and want to show that there has been confusion in Abu Hurayrah's thinking in criticizing Abu Hurayrah. This research is library research. The method is qualitative as data analysis. The results show that there are errors and defects in thinking, how can a hadith that looks odd and unreasonable, as well as a narration error, immediately justifies and asks for accountability and accuses Abu Hurayrah. Whereas in a hadith there is a series of narrators which it is possible for each narrator to make mistakes. So it is very unfair if all the blame and accusations are directed at this cat lover. This research also shows that it is reasonable, scientific and possible, for Abu Hurayrah to be the largest collector of hadith compared to other companions.